The spawning method affects the reproductive efficiency of piracanjuba fish (Brycon orbignyanus) in restocking programs - de Castro, Pedro L.; Lopera-Barrero, Nelson M.; Reis-Goes, Elenice S. dos; de Souza, Felipe P.; Bomfim, Satia C.; Julien-Ferraz, André L.; Ribeiro, Ricardo P. (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: Preserving the genetic diversity of wild fish is an important consideration for restocking programs, as inbreeding can compromise progeny survival as well as impact the resilience of natural populations. Objective: To evaluate the influence of spawning method: semi-natural (SN) or strip-spawning (ST), and the number of breeders (1♀:3♂ and 2♀:6♂) on the reproductive efficiency and genetic diversity of B. orbignyanus progeny destined for restoration of wild stocks. Methods: Rates of fertilization, hatching and broodfish mortality were recorded. For genetic evaluations (allele frequency, observed and expected heterozygosity, Shannon index, inbreeding coefficient, molecular variance analysis, and genetic differentiation), breeders (n=24), and their progenies (90 larvae/treatment) were sampled and analyzed using eight microsatellite markers. Results: Higher fertilization and hatching rates, and lower broodfish mortality were observed for the SN method (p<0.05), whereas the number of breeders did not affect these parameters (p>0.05). Interaction between spawning method and number of breeders was not significant (p>0.05). The amplified microsatellite loci produced a total of 30 alleles, with sizes between 80 and 225 bp and their frequencies indicated an increase (p<0.05) of genetic diversity in the progenies, but low genetic differentiation between treatments (p>0.05). Conclusion: The spawning methods and number of breeders tested increased equally the genetic diversity of the progeny, with low genetic differentiation between treatments. In contrast, rates of fertilization, hatching and brood fish mortality revealed that the SN method resulted in the best reproductive efficiency due to the handling stress and injuries caused by ST. Thus, SN proves to be the most suitable spawning-method for B. orbignyanus in restocking programs.